Efektivitas Metode Pembelajaran “CIBERCANTIK” dalam Meningkatkan Keterampilan Berbahasa Pada Teks Fiksi Siswa Kelas VI SDN Tegalrejo - Wahyuningsih , Devi (Najah: Journal of Research and Community Service, 2024)
This research aimed to determine the effectiveness of the "CIBERCANTIK" learning method in improving the language skills of sixth-grade students on fictional text material at SDN Tegalrejo. This method combines the use of information and communication technology with an active learning approach. This study involved 16 students as research subjects. Data was collected through participant observation and written tests. Quantitative data was analyzed using statistical tests, while qualitative data was analyzed thematically. The results showed an improvement in students' language skills after the implementation of the "CIBERCANTIK" method, as evidenced by a significant increase in various aspects of students' language skills, such as the ability to comprehend texts, analyze intrinsic elements, and express ideas orally and in writing. This is supported by the results of statistical tests that show a significant difference between the pre-test scores (M = 68.75, SD = 14.66) and post-test scores (M = 80.63, SD = 11.24). Therefore, it can be concluded that the "CIBERCANTIK" learning method is effective in improving the language skills of sixth-grade students in understanding fictional texts.